Comparison of Epidemiology and Outcomes in Neuro-Oncology Between the East and the West: Challenges and Opportunities. Issue 8 (August 2019) - Gupta, T.; Achari, R.; Chatterjee, A.; Chen, Z.-P.; Mehta, M.; Bouffet, E.; Jalali, R.
Abstract: Although neoplasms of the brain and central nervous system (CNS) are relatively uncommon, comprising only 1–2% of the overall cancer burden, they represent a substantial source of morbidity and mortality worldwide. The age-adjusted annual incidence of CNS tumours is reportedly low; however, there is substantial global variability in its incidence, with nearly a five-fold difference between regions with the highest rates in developed countries in the West and those with the lowest rates in developing countries in South-East Asia, including India, possibly attributable to key differences in environmental factors, genetic susceptibilities and cultural practices, as well as resource constraints in low–middle income countries precluding precise ascertainment and accurate diagnosis. The burden of CNS tumours is further compounded by the fact that they require highly specialised and skilled multidisciplinary care, including access to modern neuroimaging, neurosurgery, neuropathology and molecular biology, radiotherapy, chemotherapy and rehabilitation services, which may not be widely available in an integrated manner in large parts of the world with a large variation in clinical pathways, non-uniformity of care and resultant heterogeneity in clinical outcomes. CNS tumours encompass a heterogeneous spectrum of histopathological entities with differences in presentation, distinct molecular/genetic alterations, diverse biological behaviour and varying clinical outcomes. Survival is highly dependent on histology, grade and molecular biology, but varies widely across continents, even for the same tumour type and grade. In general, survival is higher in children with primary brain tumours than in adults, largely due to the differences in histological distribution across age groups. However, there is widespread variability, with 5-year survival for paediatric brain tumours being <40% in some low–middle income countries compared with 70–80% in the developed world. This review compares the descriptive epidemiology and clinical outcomes of primary brain tumours between the East and the West that pose unique challenges but also provide new opportunities in contemporary neuro-oncological practice.